An Overview of Population Growth Trends of Nepal - Regmi, Laxman Kumar (Journal of Institute of Science and Technology, 2015)
This paper aims to estimate population growth rates of Nepal and also to estimate required time period for doubling population. For this, arithmetic, geometric and exponential growth models are applied. The data are taken from the recent national censuses of Nepal. Population growth trends were 2.10% in 1971, 2.60% in 1981, 2.10% in 1991, 2.25% in 2001 and 1.35% annually in 2011. The trends of urban populations were about 4% in 1971, 6% in 1981, 9% in 1991, 14% in 2001 and 17% in 2011. The population density rose from 79 in 1971 to 181 in 2011. Urban growth rate was 7% whereas it was 2% for rural areas. The population change was found to be 40% in urban whereas 11% in rural areas during 2001-2011. However, overall change was found to be 14% during 2001-2011. The estimated growth rates were found to be 1.44%, 1.35% and 1.35% by using arithmetic, geometric and exponential respectively. The estimated time period for doubling populations was found to be 67 year by arithmetic growth model and 50 years by geometric and exponential growth model. The findings of this paper may help policy-makers and planners for designing population policy of Nepal. Journal of Institute of Science and Technology, 2014, 19(1): 52-61